(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyzes the territorial articulation process occurred from the discovery and exploitation of various salt efflorescence near the northwestern Zacatecas and San Luis Potosi in the second half of the sixteenth century. The commercialization of salt from the Salinas de Santa Maria and Salinas del Peñol Blanco, not only boosted mine production of Zacatecas and other areas such as Pachuca and Guanajuato, but in the same way, under this commercial momentum other compulsive mechanisms were Developer, aimed to regulate the transfer of indigenous workers enrolled in the district of Tlaltenango. This comprehensive process, little studied, on the other hand, allows us to understand how that throughout this period the salt extraction (necessary element for the amalgamation of silver by the method of patio) acquired a remarkable range of expertise and generated a territorial configuration process in the Septentrion of the New Spain.